Citra Perempuan dalam Tayangan Iklan TV - Fathiyah; Nur Fahmi Hidayah (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Advertising is an important part of marketing activities, with the ability ofadvertising to build the image of a product able to attract the attention ofpotential consumers. Television advertisements display women in images as sexobjects and decoy. Women as sex objects sre displayed in the form of women’sdomestic roles, while images as a decoy are displayed in the form of sexualexploitation to attract the attention of consumers.